Analisis Daya Tahan Fisik (Tingkat VO_2 Max) Siswa SD Bina Insan Cendekia Kota Pasuruan - Nur An-Nisaa'; Wiwik Kusmawati; Rubbi Kurniawan; Anangga Widya Pradipta; Sudari; Budijanto (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study aims to determine the physical endurance (VO₂Max level) of students at Bina Insan Cendekia Elementary School, Pasuruan City. VO₂Max is the main indicator in assessing a person's aerobic capacity, which plays a very important role in physical performance, especially in sports that require high endurance. This study is a descriptive study with a quantitative approach. The population in this study were all students at Bina Insan Cendekia Elementary School, Pasuruan City in the 2024/2025 academic year. The sample of this study was all 5th grade students of Bina Insan Cendekia Elementary School, Pasuruan City, totaling 30 people. The data analysis technique used was descriptive statistical data analysis, with data presentation through tables. The average VO₂Max of Bina Insan Cendekia Elementary School students, Pasuruan City, was in the moderate category with a value of 40.17 ml/kg/minute.